1989
DOI: 10.1128/aac.33.3.277
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo uptake of azithromycin (CP-62,993) by phagocytic cells: possible mechanism of delivery and release at sites of infection

Abstract: Azithromycin, a novel azalide antibiotic, concentrated in human and mouse polymorphonuclear leukocytes (PMNs), murine peritoneal macrophages, and mouse and rat alveolar macrophages, attaining intracellular concentrations up to 226 times the external concentration in vitro. In murine peritoneal macrophages, azithromycin achieved concentration gradients (internal to external) up to 26 times higher than erythromycin. The cellular uptake of azithromycin was dependent on temperature, viability, and pH and was decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
325
4
6

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 444 publications
(348 citation statements)
references
References 20 publications
13
325
4
6
Order By: Relevance
“…However, after 24 hours of incubation in drug-free medium, Ͼ90% of intracellular drug was released into the medium ( Figure 3). 8 More recently, studies using rat embryo fibroblasts and epithelial-like rat kidney cells have confirmed these results. 5 Thus, the opposing forces of intracellular accumulation and extracellular release create a dynamic equilibrium, resulting in the high, sustained tissue concentrations and long half-life characteristic of azithromycin.…”
Section: A6mentioning
confidence: 80%
See 3 more Smart Citations
“…However, after 24 hours of incubation in drug-free medium, Ͼ90% of intracellular drug was released into the medium ( Figure 3). 8 More recently, studies using rat embryo fibroblasts and epithelial-like rat kidney cells have confirmed these results. 5 Thus, the opposing forces of intracellular accumulation and extracellular release create a dynamic equilibrium, resulting in the high, sustained tissue concentrations and long half-life characteristic of azithromycin.…”
Section: A6mentioning
confidence: 80%
“…In human fibroblasts and mouse macrophages, the entry of drug into the cell is rapid, and the intracellular concentration is proportional to both time of incubation and extracellular concentration (Figure 2). 4,8 This linear relationship suggests a nonsaturable process. Inhibitors of glycolysis and oxidative metabolism do not affect the entry process, nor is it affected by inhibitors of known membrane-transport systems for nucleosides, hexoses, or amino acids.…”
Section: A5mentioning
confidence: 98%
See 2 more Smart Citations
“…Azithromycin is a dicationic derivative of erythromycin A [1,2] which avidly accumulates in tissues [3,4] and in cultured mammalian cells, reaching intracellular to extracellular concentrations ratios of 100 and more [5]. Cell fractionation studies show that the bulk of the drug accumulated by cells localizes in the lysosomes [6].…”
Section: Introductionmentioning
confidence: 99%